The Biosynthesis of Cyclopropane Fatty Acids - Buist, Peter H. (My University, 1980)
Mechanistic information has been obtained for biological cyclopropane fatty acid formation by L. plantarum. Deuterium labelling studies showed that when a methylene bridge is constructed across the double bond of an olefinic fatty acid, no scrambling or loss of label occurs at the vinylic or the allylic position of the olefin. One of the consequences of these results is that any mechanism whereby the olefin is activated at the allylic position has been conclusively ruled out.
Up to 18% of a d₁-cyclopropyl fatty acid was formed in feedings using methionine-methyl-d₃. It was shown that exchange had not occurred at the methionine stage. Exchange of a protonated cyclopropane intermediate is postulated to account for the production of d₁-cyclopropyl product.
An intermolecular primary deuterium isotope effect of 1.07 ± 0.04 and a minimum intramolecular primary deuterium isotope effect of 3.2 ± 0.5 was measured for the proton abstraction step. Thus, carbon-hydrogen bond cleavage is not a rate-limiting step in the biological cyclopropanation reaction.
A mechanism involving methylation of an olefin followed by 1,3-proton elimination is favoured for the biological formation of cyclopropane fatty acids.
Keywords: Chemistry; Chemistry